Book review of Capital in the Twenty-First Century, by Thomas Piketty. Cambridge, Massachusetts, London, England: The Belknap Press of Harvard Press, 2014, 605 pages - Paul Dobrescu; Mălina Ciocea (Romanian Journal of Communications and Public Relations, 2015)
“Every now and then, the field of economics produces an important book; this is one of them” (Cowen, 2014). These are the opening words of Tyler Cowen’s presentation of Thomas Piketty’s work, “Capital in the Twenty-First Century” (Piketty, 2014), in Foreign Affairs. This is a book that is visibly placed in all important bookstores around the world, widely debated, acclaimed, sold (over 1 million copies have been sold so far). It has been favorably reviewed or quoted in all major journals. The assessment of “Capital in the Twenty-First Century” by Paul Krugman, Nobel Economics Prize Laureate as a “magnificent, sweeping meditation on inequality”, is highly relevant: “This is a book that will change both the way we think about society and the way we do economics” (Krugman, 2014). Finally, Piketty’s book is included in the list of the year’s best books by prestigious journals, such as The Economist, Financial Times, The Washington Post, Observer, The Independent, Daily Telegraph; Financial Times and McKinsey have hailed it as the best book of 2014.